Time-dependent wave packet study of the N++H-2 reaction - Russell, C; Manolopoulos, D (1999)
The time-dependent wave packet method has been used to calculate initial state selected reaction probabilities, reaction cross sections, and rate constants for the N++H2 reaction on the potential energy surface of Wilhelmsson, Siegbahn, and Schinke [J. Chem. Phys. 96, 8202 (1992)]. In addition to providing results that can be used to test more approximate theories, these calculations are used to shed light on a number of key issues concerning the reaction, including the correct value of the reaction endothermicity, the reactivity of excited H2 rotational states, and the lifetimes of the intermediate NH2+ complexes that are formed in collisions of N+ with H2(v=0) and H2(v=1). We also show that an earlier quasiclassical trajectory study of the reaction on the same potential energy surface predicted the wrong cross-section behavior in the threshold region as a result of an incorrect treatment of product zero-point energy. © 1999 American Institute of Physics.